"Not shifting, but sharing": stakeholders' perspectives on mental health task-shifting in Indonesia - Ferry Efendi; Gading Ekapuja Aurizki; Ah Yusuf; Lisa McKenna (BMC, 2022)
Abstract Background Task-shifting, the distribution of tasks among health workers to address health workforce shortage, has been widely used to tackle mental health treatment gaps. However, its implementation in Indonesia has still been rarely explored. This study aimed to explore stakeholders' perspectives on the implementation of mental health task-shifting to nurses in Indonesia's primary health care. Methods An exploratory descriptive approach using in-depth interviews and focused group discussions (FGDs) was used. The study involved 19 stakeholders from the government's ministry directorates, professional organisations, and mental health practitioners. Thematic analysis was used to analyse the data. Results Three themes emerged namely, task-shifting feasibility and acceptability, shared task implementation, and nurse role enhancement issues, with 14 sub-themes. Conclusions Task-shifting on mental health issues in the eye of Indonesian stakeholders is viewed as a matter of sharing and collaboration. Implementation of task-shifting in Indonesia may require policies in place and political will across stakeholders. Further scrutiny on task-shifting implementation is needed by considering the local context and national environment.